Implementasi Pembelajaran Tahfidz Al-Qur’an Bagi Siswa Inklusi - M Berian Purnama; Rahmi Wiza (An-Nuha, 2022)
This study aims to determine the implementation of Tahfidz Al-Qur’an learning for inclusive students at SD IT AlIffat Payakumbuh City. This research uses qualitative methods with the type of field research. Sources of research data are Ustadz/Ustadzah teachers and several students. Data collection techniques used in this study were observation, in-depth interviews, and documentation. The validity of the research data was tested by using triangulation and persistence techniques. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the implementation of Tahfidz Al-Qur’an which was applied to students was going well.